(untitled) (International Journal of Engineering and Computer Science, 2016)
Cellulose based non conducting materials and mineral oils have widely been used in liquid filled transformers. Environmental and fire-safety concerns have accelerated the use of Natural Esters (NE) as a sustainable alternative to mineral oil. To ensure a safe and long-term operation of the vegetable oil filled transformers, it is need to clarify the knowledge gaps with respect to the ageing of vegetable oil impregnated cellulose and insulation diagnostic methods. The condition monitoring of mineral oil filled transformers has been well characterised, due to the numerous laboratory and field studies conducted during the past several decades. The application of these available condition monitoring techniques for NE filled transformers is yet to be validated as the use of NE for power transformers is in the tested stage. In this paper the performance of NE as insulation in transformers by evaluating the ageing of NE impregnated cellulose pressboard is presented. For this purpose, an accelerated ageing experiment has been carried out in sealed tubes at 120 ⁰C. The ageing of oil impregnated pressboard has been characterised by decrease in the degree of polymerisation (DP) of pressboard, and the formation of both 2-furfuraldehyde and dissolved carbon dioxide (CO2) in the oil. The structural changes of cellulose have been supported by fuzzy logic algorithm. Moreover, the results have been compared with cellulose insulation samples aged under similar conditions in conventional mineral oil.